‘There’s nothing you can do…it’s like that in Chinatown’: Chinese immigrant women’s perceptions of experiences in Chicago Chinatown healthcare settings - Simon, Melissa A. (Ethn Health, 2019)
OBJECTIVES. Chinese American women living in linguistically-isolated communities are among the least likely to utilize healthcare services. Qualitative research methods can help identify health system vulnerability points to improve local healthcare delivery for this population. DESIGN. We conducted six focus groups among 56 Chinese-speaking adult women in Chicago’s Chinatown between July – August 2014 to explore their perceptions of experiences receiving medical care and interacting with healthcare providers in Chinatown healthcare settings. RESULTS. Health system/clinic infrastructure and patient-provider communications were perceived barriers to care at Chinatown healthcare settings. Chinese participants reported long wait times, difficulty scheduling appointments, and poor front desk customer service. Communication difficulties at Chinatown healthcare settings involved language barriers with non-Chinese speaking providers, but consideration for healthcare providers, provider demeanor, and reliance on provider recommendation also hindered patient-provider communications. CONCLUSIONS. Findings improve understanding of barriers to care experienced by Chinese immigrant women in one urban Chinatown community.